Identification of the Key Odorants in Clean Aroma-Type Xinyang Maojian Green Tea - YIN Peng, WEI Yiwei, WANG Jing, WANG Xiao, ZHANG Xiangna, SU Dan, WANG Jingjing, SUN Mufang, GUO Guiyi, LIU Zhonghua (Shipin Kexue)
In this study, gas chromatography-olfactometry-mass spectrometry (GC-O-MS) combined with odor activity value (OAV) was used to analyze the key odorants of clean aroma-type Xinyang Maojian (XYMJ) green tea. The results of aroma extract dilution analysis (AEDA) showed that 48 volatile compounds were obtained from XYMJ green tea infusion by solvent-assisted flavor evaporation (SAFE) and headspace-solid phase microextraction (HS-SPME). Twenty-two volatile compounds with flavor dilution (FD) factor ≥ 27 were identified. Among these, dihydroactinidiolide showed the highest FD factor (6 561), followed by vanillin (2 187), coumarin (729), 2-phenylethanol (729), hexanal (243), 4-hydroxy-2,5-dimethylfuran-3(2H)-one (243) and δ-decalactone (243). Through quantitative analysis, we identified 17 key odorants with OAV > 1, including (E,Z)-2,6-nonadienal, dimethyl sulfide, 3-methylbutanal, geraniol, (E)-β-ionone, linalool, 6-methyl-5-hepten-2-one, (E,E)-2,4-heptadienal, hexanal, 2-methylbutanal, jasmone, nonanal, δ-decalactone, γ-hexalactone, coumarin, δ-jasmolactone and indole. The OAV values indicate that these key odorants make important contributions to the aroma quality of clean aroma-type XYMJ green tea.